Void nucleation during ductile rupture of metals: A review. (June 2023) - Noell, Philip J.; Sills, Ryan B.; Benzerga, Ahmed Amine; Boyce, Brad L.
Abstract: Ductile rupture in metals is a phenomenon that affects a wide range of applications from forming of automotive body panels to failure of pressure vessels. The incipient stage involves the formation of nanoscale internal voids, a critical transition state that is difficult to predict. Early experiments on ductile rupture led to several conflicting or competing models that describe the nucleation phase. The present review distinguishes the nucleation process based on the microstructural features that can trigger nucleation, e.g. vacancies, second-phase particles, grain boundaries, and dislocation cell boundaries; the conditions that drive nucleation, e.g. stress level, stress state, and temperature; and the materials properties that govern nucleation, e.g. modulus, yield strength, and work hardening. This review of observations and models leads to a critical assessment of the state of knowledge and provides guidance for future research directions, including a brief summary of the potential mechanistic changes to void nucleation processes in emerging material classes such as bulk metallic glasses, high entropy alloys, and nanostructured metals. This assessment also defines critical experiments and model developments that will enable improved prediction of ductile rupture processes and design of damage-tolerant materials. Such improvements in the understanding of the incipient phase of ductile rupture can lead to better materials, improved manufacturing and inspection protocols, more precise predictive models, more efficient engineering practices, and safer engineered structures.